Spelling errors in official letters in the Ciracas area East Jakarta - Sri Mulyani (Universitas Indraprasta PGRI, 2018)
The purpose of this research is to describe spelling errors in the official letter in ciracas area, East Jakarta written since February —- November 2017 while the method used in this research, that is descriptive qualitative. Data collection techniques by collecting six letters of service. After research on six official letters from the